International practice analysis of the negative list: Chinese Example of shipping market access - Shi, Yuanhong (Frontiers in Marine Science, 2023)
The international shipping industry is unique and important. The negative list related to the opening up of the shipping industry is an important part of the reform and innovation of China’s pilot free trade zones. In recent years, as countries around the world continue to promote the process of opening up in the fields of trade and services, the negative list system has been used more in international investment and trade agreements. In the field of International Shipping, how to correctly grasp and apply the negative list system is an important topic. Starting with the general concept of the negative list system of shipping market access, this paper reviews and summarizes the developmental processes of the negative list of foreign capital market access in the shipping field since the establishment of Shanghai Pilot Free Trade Zone. It compares and analyzes the international contracting practice of the European Union and the United States as reflected in the negative list of shipping market access. It equally points out that the system connection between the negative list still existing in China’s shipping field and the international high standard negative list is not enough. It argues that the transparency of the negative list still needs to be further strengthened, as the rules behind the list and the awareness of its risk prevention are weak. In view of these hitches, this paper makes some suggestions that are tilted towards improving the negative list system of China’s shipping market access. It also continues the optimization of the negative list of shipping market access and the improvement of a conscious awareness aimed at avoiding the possible risks of the negative list. Finally, it makes a strong argument for a continuous improvement of China’s international shipping competitiveness.